Plant and Soil Enzyme Activities Regulate CO2 Efflux in Alpine Peatlands After 5 Years of Simulated Extreme Drought - Yan, Zhongqing; Kang, Enze; Zhang, Kerou; Li, Yong; Hao, Yanbin; Wu, Haidong; Li, Meng; Zhang, Xiaodong; Wang, Jinzhi; Yan, Liang; Kang, Xiaoming (Frontiers in Plant Science, 2021)
Increasing attention has been given to the impact of extreme drought stress on ecosystem ecological processes. Ecosystem respiration (Re) and soil respiration (Rs) play a significant role in the regulation of the carbon (C) balance because they are two of the largest terrestrial C fluxes in the atmosphere. However, the responses of Re and Rs to extreme drought in alpine regions are still unclear, particularly with respect to the driver mechanism in plant and soil extracellular enzyme activities. In this study, we imposed three periods of extreme drought events based on field experiments on an alpine peatland: (1) early drought, in which the early stage of plant growth occurred from June 18 to July 20; (2) midterm drought, in which the peak growth period occurred from July 20 to August 23; and (3) late drought, in which the wilting period of plants occurred from August 23 to September 25. After 5 years of continuous extreme drought events, Re exhibited a consistent decreasing trend under the three periods of extreme drought, while Rs exhibited a non-significant decreasing trend in the early and midterm drought but increased significantly by 58.48% (p < 0.05) during the late drought compared with the ambient control. Plant coverage significantly increased by 79.3% (p < 0.05) in the early drought, and standing biomass significantly decreased by 18.33% (p < 0.05) in the midterm drought. Alkaline phosphatase, polyphenol oxidase, and peroxidase increased significantly by 76.46, 77.66, and 109.60% (p < 0.05), respectively, under late drought. Structural equation models demonstrated that soil water content (SWC), pH, plant coverage, plant standing biomass, soil β-D-cellobiosidase, and β-1,4-N-acetyl-glucosaminidase were crucial impact factors that eventually led to a decreasing trend in Re, and SWC, pH, β-1,4-glucosidase (BG), β-1,4-xylosidase (BX), polyphenol oxidase, soil organic carbon, microbial biomass carbon, and dissolved organic carbon were crucial impact factors that resulted in changes in Rs. Our results emphasize the key roles of plant and soil extracellular enzyme activities in regulating the different responses of Re and Rs under extreme drought events occurring at different plant growth stages.